2020
DOI: 10.1097/inf.0000000000002638
|View full text |Cite|
|
Sign up to set email alerts
|

High Frequency of Aichivirus in Children With Acute Gastroenteritis in Iran

Abstract: Background: Initially, detection and isolation of Aichivirus as a new member of Picornaviridae family was documented in Japan. Aichivirus species belongs to genus Kobuvirus, including 3 genotypes A, B and C. In previous studies, it has been suggested that Aichivirus infect humans by fecal-oral route. To establish an investigation for the occurrence of Aichivirus among pediatric patients involved to acute gastroenteritis, we developed a reverse transcription quantitative polymerase chain reaction as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Regarding SaV and AiV, we observed a relative seasonal distribution throughout the sampling period with a peak during the dry season for SaV and the occurrence of AiV in April and November. These findings are in line with the results described in previous studies reporting SaV seasonal distribution with a peak in the dry season, and high seasonal distribution of AiV infections in January, February, and December [22,39].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding SaV and AiV, we observed a relative seasonal distribution throughout the sampling period with a peak during the dry season for SaV and the occurrence of AiV in April and November. These findings are in line with the results described in previous studies reporting SaV seasonal distribution with a peak in the dry season, and high seasonal distribution of AiV infections in January, February, and December [22,39].…”
Section: Discussionsupporting
confidence: 93%
“…AiVs were suggested to play a role in GE, especially in outbreaks caused by contaminated seafood [21]. Human pathogenic AiVs belonging to the genus Kobuvirus were classified as AiV-1 and are divided into three different genotypes (A-C) [22], with little information available about their geographical distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Aichi virus (AiV), a subtype of the species Aichivirus A (genus Kobuvirus) (Rivadulla and Romalde 2020), was first isolated in 1989 during an outbreak of oyster-associated gastroenteritis in Japan (Yamashita et al 1991) and has since been detected worldwide (Oh et al 2006;Sdiri-Loulizi et al 2009;Yang et al 2009;Chuchaona et al 2017;Bergallo et al 2018;Kitajima et al 2018;Japhet et al 2019;Onosi et al 2019;Northill et al 2020). Globally, the incidence rates of AiV in gastroenteritis cases are low (0.4-6.5%) (Rivadulla and Romalde 2020;Taghinejad et al 2020), yet AiV-specific antibodies are present in 80-99% of the adult population (Kitajima and Gerba 2015) suggesting that most infections are asymptomatic (Bergallo et al 2018). In addition to the low prevalence of AiV-associated gastroenteritis, the virus is often detected in conjunction with other welldefined enteric pathogens (Oh et al 2006;Ambert-Balay et al 2008;Kaikkonen et al 2010;Japhet et al 2019).…”
Section: Picornaviruses: Enteroviruses Aichivirus and Hepatitis A Virusmentioning
confidence: 99%
“…A PRISMA‐based flow diagram in Figure 1 shows the search and studies selection process. Out of the total 306 potentially related studies found in the initial search, after removing studies that were duplicate or did not meet the inclusion criteria, 12 studies (15 data sets) remained, which includes six case‐control studies 3,8,21–24 and seven cross‐sectional studies 6,7,9,21,25–27 . In the present study, 8976 subjects were studied (4526 subjects in cross‐sectional and 4450 case‐control design studies) from 13 countries (Tunisian, USA, Nepal, China (2), Denmark, Brazil, India, Nigeria, Hong Kong, Germany, Thailand, Italy and Iran).…”
Section: Resultsmentioning
confidence: 99%
“…According to different reports from various geographical regions, the prevalence of SaV was varied, Tunisia (1%), Italy (0.5%), Thailand (0.44%), Hong Kong (0.07%), Iran (0.7%), Brazil (1.7%) and 3.8% in Germany 6,7,9,23,27,29 . The results of reviewed studies about the association between SaV and GI complications contrast with each other.…”
Section: Discussionmentioning
confidence: 99%